Isle of dogs - Wilford, Lauren; Ramos, Taylor; Seitz, Matt Zoller; Zhou, Tony; Stevenson, Ryan (Writer on film) (New York Abrams, 2018)
The Wes Anderson Collection: Isle of Dogs is the only book to take readers behind the scenes of the beloved auteur's newest stop-motion animated film. Through the course of several in-depth interviews with film critic Lauren Wilford, writer and director Wes Anderson shares the story behind Isle of Dogs's conception and production, and Anderson and his collaborators reveal entertaining anecdotes about the making of the film, their sources of inspiration, the ins and outs of stop-motion animation, and many other insights into their moviemaking process. Previously unpublished behind-the-scenes photographs, concept artwork, and hand-written notes and storyboards accompany the text. The book also features an introduction by critics and collaborators Taylor Ramos and Tony Zhou, and a foreword by critic Matt Zoller Seitz. The fourth volume of the New York Times bestselling Wes Anderson Collection, Isle of Dogs stays true to the series with its rich design and colorful illustrations, capturing Anderson's signature aesthetic vision and bringing the series's definitive study of Anderson's filmography up to date.
Includes bibliographical references
Keywords: Anderson, Wes; Isle of dogs (Motion picture : 2018).; Animation (Cinematography); Performing Arts -- Film & Video -- General